Biomechanics of the taekwondo axe kick: a review - Mailapalli, D.; Benton, J.; Woodward, T. W. (Journal of Human Sport & Exercise, 2015)
The axe kick in Taekwondo has been observed to be a highly effective offensive and defensive technique. Its purpose is to attack the opponent`s head, collarbone or chest with a powerful downward force. However, few researchers have studied the biomechanics of this kicking technique. The modified competition rules of World Taekwondo Federation (WTF) on the number of points to the head resulted increase in the number of kicks to the head by athletes using the axe kick. Therefore it is important to know the biomechanical principles of the axe kick for executing the kick effectively with minimum injury to the opponent`s head, collarbone or chest and for scoring maximum number of points in a competition. The main purpose of this article is to present a general description, variations and biomechanics of the Taekwondo axe kick. See more at: http://www.jhse.ua.es/jhse/article/view/853#sthash.Ip1oRRQP.dpuf